Storage of Pre-treated Ash Gourd Seeds - C. MINI; JYOTHILEKSHMI UNNIKRISHNAN (Seed Research, 2026)
Pre-treated seeds are better in performance compared to untreated seeds. Though there was a gradual decrease in quality parameters like, percentage germination, speed of germination and vigour index. Seeds pre-treated with growth regulators can be safely stored for a period up to five months. This clearly indicates that pre-treated seeds can be directly supplied to farmers for immediate use. Seeds treated with GA, 25 ppm and KNO, are not safe for storage.